2005
DOI: 10.1002/path.1763
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of a morphogen (sonic hedgehog) gradient in the gastric epithelium of Helicobacter pylori‐infected Mongolian gerbils

Abstract: Sonic hedgehog (Shh) is a morphogen involved in many aspects of patterning of the gut during embryogenesis and in gastric fundic gland homeostasis in the adult. Intestinal metaplastic change of the gastric epithelium is associated with the loss of Shh expression, and mice that lack Shh expression show intestinal transformation of the gastric mucosa. The present study was designed to investigate the alteration of Shh expression in the stomach of an experimental model of Helicobacter pylori (H. pylori) colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 26 publications
8
79
0
Order By: Relevance
“…Substantial evidence has shown that the Shh pathway is crucial to the development and homeostasis of gastric glands. In addition, abnormal activation of the Shh pathway has been found toresult in gastric cancer (12)(13)(14).The aim of the present study was to investigate the effects of metformin on the regulation of the Shh signaling pathway in gastric cancer cells. The expression levels of Shh, Glioma associated oncogene (Gli)-1, Gli-2 and Smoothened (SMO) were examined using western blot and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Substantial evidence has shown that the Shh pathway is crucial to the development and homeostasis of gastric glands. In addition, abnormal activation of the Shh pathway has been found toresult in gastric cancer (12)(13)(14).The aim of the present study was to investigate the effects of metformin on the regulation of the Shh signaling pathway in gastric cancer cells. The expression levels of Shh, Glioma associated oncogene (Gli)-1, Gli-2 and Smoothened (SMO) were examined using western blot and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses.…”
mentioning
confidence: 95%
“…Substantial evidence has shown that the Shh pathway is crucial to the development and homeostasis of gastric glands. In addition, abnormal activation of the Shh pathway has been found toresult in gastric cancer (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In the claudin‐18‐KO mouse, acid backflux from the gland lumen also causes parietal cell loss, but this occurs within the first days of life 10. A similar, albeit delayed, parietal cell loss followed by fundic hyperplasia and inflammatory cell infiltration occurs in the occludin‐KO mouse 36, 43. In the CAIX‐KO gastric mucosa, the only significant abnormality detected by us at one month of age was an increase in the gastric mucosal IL‐1 β and iNOS expression, and the strong decrease in claudin‐18 expression (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 95%
“…As for unsolved questions that how hypertrophic gastritis develops under the prominent pathological background of atrophic gastritis associated with H. pylori infection [4] or how the attenuated levels of sonic hedgehog (Shh) observed up to the development of precancerous lesions turned into increased expressions in gastric cancer [12,13], we speculates two possibilities; one is the emergence or reactivation of cell clones harboring apoptosis resistant characteristics even under prevailing apoptosis after H. pylori infection and the other is the enormous expansion of cell clone possessing proliferative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all of these cancers arise from the tissues where Shh signaling plays an important developmental role. Since the loss of Shh is an indicator of H. pylori-induced atrophic gastritis mechanistically through either promoter methylation or loss of Shh expressing cells by gastric inflammation and increased expression of Shh was noted in gastric cancer [13,14], we hypothesized that the reemergence of cell clones carrying Shh after H. pylori infection might contribute to the resistance to apoptosis, providing the chance to proliferative activities under the milieu of H. pylori-induced atrophic gastritis.…”
Section: Introductionmentioning
confidence: 99%